2011
DOI: 10.4028/www.scientific.net/amr.230-232.1231
|View full text |Cite
|
Sign up to set email alerts
|

Hydroscopic and Mechanical Properties Performance Analysis of Rice Husk Powder/PLA Composites

Abstract: The rice husk powder was modified by polymer (lactic acid) (PLA) and Maleic anhydride (coupling agent, MAPP). Composite material was prepared in the way of melt blending. The mechanical properties, water absorbability of rice husk/polymer (lactic acid) (PLA) composites, and the relations between these properties and microscopic characteristics were investigated. The result showed that, with the increasing content of rice husk power, the maximum bearable tension and tensile strength increased; Water absorbabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Consequently, the heat treatment did not provide any improvement to the hardness with the fi ller concentration of 10 % and 30 %. Similar results for wood reinforced polymer composites were also observed by Hua et al (2011), Kord (2011), Medupin et al (2013) and Sathishkumar (2014).…”
Section: Resultssupporting
confidence: 86%
“…Consequently, the heat treatment did not provide any improvement to the hardness with the fi ller concentration of 10 % and 30 %. Similar results for wood reinforced polymer composites were also observed by Hua et al (2011), Kord (2011), Medupin et al (2013) and Sathishkumar (2014).…”
Section: Resultssupporting
confidence: 86%
“…In research by Hua et al [50], the rice husk powder (RHP) was modified by PLA using melt-blending technique, and MAPP was used as coupling agent. The mechanical properties, water absorbability of RHP/PLA composites, and the relations between these properties and microscopic characteristics were investigated.…”
Section: Rice Husk/polylactic Acid Compositesmentioning
confidence: 99%
“…As a result, compatibility of the RH‐matrix was developed leading to enhanced mechanical properties of the composites. It was found that RH can improve the maximum tolerable, tension, tensile strength, and water absorptivity of PLA/RH composites 19 . By investigation of its complex dielectric permittivity range and loss tangent, Zawawi et al 20 confirmed that RH/PLA composites can be used for microwave applications.…”
Section: Introductionmentioning
confidence: 98%